(untitled) (LEGAL DIALOGICA, 2025)
This research aims to understand and analyze how the authority granted to the Regional Representative Council (DPD) in the Indonesian constitutional system should be viewed from the perspective of a bicameral parliamentary system. This study will employ a conceptual and comparative approach to address the issues raised. The research uses a normative legal research method, with primary sources being applicable laws and regulations, and secondary sources including legal materials such as literature, books, scholarly articles, journals, academic manuscripts, and opinions of experts in the relevant legal field. The results of this research indicate that the regulation of the authority of the Regional Representative Council (DPD) in Indonesia over time shows a stagnant dynamic, starting from its establishment which was half-hearted and subsequently affecting its limited authority, until now the authority of the DPD remains a constitutional issue in Indonesia. Starting from limited authority, check and balance, political stability, representation, professionalism, representation, and this balance of power causes the functions of the Regional Representative Council (DPD) to be less effective in reconstructing regional interests, thus that authority needs to be strengthened, evaluated, and equated with the People’s Representative Council (DPR) through amendments. Abstrak: Penelitian ini bertujuan untuk memahami dan menganalisis bagaimana seharusnya kewenangan yang diberikan kepada Dewan Perwakilan Daerah (DPD) dalam sistem ketatanegaraan Indonesia ditinjau dari sistem parlemen dua kamaar (bicameral). Penelitian ini akan menggunakan pendekatan konseptual dan perbandingan guna menjawab persoalan yang diajukan. Penelitian ini menggunakan metode penelitian hukum normatif, dengan sumber primer berupa peraturan perundang-undangan yang berlaku secara umum dan hukum. Sumber sekundernya adalah bahan-bahan hukum seperti literatur, buku-buku, karya ilmiah, jurnal, naskah akademis, dan pendapat para ahli di bidang hukum terkait. Hasil penelitian ini menunjukkan bahwa pengaturan kewenangan Dewan Perwakilan Daerah (DPD) di Indonesia dari masa ke masa menunjukkan dinamika yang stagnan, mulai pada saat pembentukannya yang setengah hati kemudian memperngaruhi kewenangannya yang terbatas, hingga saat ini kewenangan DPD masih menjadi masalah ketatanegaraan di Indonesia mulai dari kewenangan yang terbatas, check and balance, stabilitas politik, keterwakilan, profesionalitas, representasi, dan keseimbangan kekuasaan ini menyebabkan fungsi DPD menjadi kurang efektif dalam merekonstruksi kepentingan daerah, sehingga kewenangan tersebut perlu diperkuat, dievaluasi dan disetarakan dengan Dewan Perwakilan Rakyat (DPR) melalui amandemen.